Clinico-Epidemiological Characteristics Of Chronic Heart Failure Morbidity In The Population Of Andijan City - Sobirova Khanifabonu Norkuzi kizi (Zien Journals, 2025)
This article analyzes the clinical and epidemiological characteristics of chronic heart failure (CHF) morbidity in the population of Andijan city. The study examines prevalence rates across different age and gender groups, identifies key risk factors and explores the clinical manifestations of the disease. The findings provide valuable insights into the epidemiological situation of chronic heart failure, serving as a scientific basis for improving preventive strategies in public health and enhancing the quality of diagnosis and treatment in clinical practice
Keywords: Andijan city; chronic heart failure; clinical characteristics